PENERAPAN HYGIENE SANITASI MAKANAN PADA DAPUR MBG DI KABUPATEN X - Chantika Kharisma Ramadhani; Linda Suwarni; Selviana; Helfi Nolia (Poltekkes Kemenkes Medan, 2025)
Improving the nutritional quality of schoolchildren is a key government priority, and the Free Nutritious Meal Program (MBG) has been implemented in District X to support this effort. Ensuring proper food hygiene and sanitation is essential to safeguard food safety and program sustainability. This descriptive observational study examined the implementation of hygiene and sanitation practices in the MBG Program, including raw material selection, food processing, packaging, distribution, and cleanliness. The study also assessed the knowledge and attitudes of food handlers responsible for preparing 3,300 daily portions for kindergarten, elementary, junior high, and senior high school students. Data were collected through surveys, observations, and interviews with 14 representatives of the MBG kitchen team in District X. Most food handlers demonstrated good knowledge (78.6%) and supportive attitudes (92.9%) toward hygiene and sanitation. However, handwashing practices and the use of personal protective equipment (PPE) were inconsistently applied, and the use of closed footwear was low (35.7%). Key challenges included inadequate food storage practices, serving times exceeding standards, high workloads, and limited facilities. Although the MBG Program is functioning relatively well, continuous training, additional staffing, improved facilities, and better scheduling systems are required to strengthen food safety and enhance program quality..